Olympic education in all Greek schools: adoption and abandonment - Costas Mountakis (Karolinum Press, 2016)
Prior to the Olympic Games of 2004, Greece incorporated Olympic Education into the curriculum of its national educational system for one session per week in every grade from the ages of 6 to 18. The main forces behind this were: the International Olympic Academy, the International Foundation of Athletic and Sports Education, the Pedagogical Institute of Greece, the Ministry of National Education and Religious Affairs, and the Organizing Committee of the Olympic Games 'Athens 2004'. Their main activity was in producing a programme of teaching materials, and the centralized nature of the educational system enabled the programme to be introduced in a very short time. The programme continued to be implemented in schools after the Olympic Games in the primary sector, and also as an option at the secondary level, under the name of 'Kallipatira'. The programme lasted after the Olympic Games and up to the 2007-2008 school year. During the 2008-2009 school year, however, it was removed from the curriculum. This paper presents an account of the way in which the programme was introduced into schools, which may be used as a model or guide for any other country organizing the Olympic Games.